Religious Demographics of Pharmacy Ownership in Northeast India: A Comprehensive Analysis of Assam’s Shifting Landscape (2015-2023) - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: The pharmaceutical retail sector in Northeast India has undergone significant transformation in recent decades, with changing patterns of ownership across different religious communities. This study examines the demographic composition of pharmacy ownership in Assam compared to other Northeastern states, with particular attention to religious affiliation patterns and their implications for healthcare access, equity, and culturally-responsive service delivery. Methods: We employed a mixed-methods approach combining: (1) analysis of Pharmacy Council registration records from all Northeast Indian states (2015-2023); (2) structured surveys of 678 pharmacy owners across 15 districts in Assam; (3) 47 semi-structured interviews with key stakeholders including regulatory officials, pharmacy educators, and community leaders; and (4) geospatial mapping of pharmacy distribution patterns with demographic overlay analysis. Religious affiliation was determined through self-reporting and verified against registration documentation. Chi-square tests, multivariate logistic regression, and geospatial clustering analyses were utilized to analyze demographic patterns and identify associated factors. Results: Analysis of 3,875 pharmacy registrations across Northeast India revealed significantly higher representation of Muslim pharmacists in Assam (43.7%) compared to other Northeastern states (average 12.8%, p<0.001). Within Assam, Muslim ownership increased from 28.5% in 2015 to 43.7% in 2023, with pharmacy density per population highest in Lower Assam districts. After adjusting for population demographics, educational attainment, urbanization, and socioeconomic indicators, Muslim ownership representation exceeded demographic proportions in 21 of 33 districts (OR=1.76, 95% CI: 1.54-2.01). Thematic analysis of qualitative interviews revealed four key pathways into pharmacy ownership: educational advancement strategies, family business continuity, professional autonomy seeking, and community healthcare service motivations, with varying prevalence across religious groups. Conclusion: This study documents the substantial and growing representation of Muslim pharmacists in Assam's pharmaceutical sector compared to other Northeast Indian states. This trend reflects complex socioeconomic factors including educational investment patterns, professional preferences, and healthcare entrepreneurship within religious communities. The findings have implications for culturally responsive pharmaceutical care, equitable healthcare workforce development policies, and community-based healthcare delivery in religiously diverse regions.